Osteoarthritis of the hands in a rural population : (Anthropological Research on the Island of Brač, Croatia) : Doctoral Dissertation - Lethbridge Cejku, Margaret (M. Lethbridge Cejku, 1995)
Summary: The objectives of this research are to examine the prevalence and pattern of radiographic osteoarthritis (OA) of the hand joints in a normal, community-dwelling adult population, and to analyze the relationship of hand OA to other risk factors, independet of age effects or gender differences. This study also aims to examine inter-population diferences which are not related to either age or occupation, among the villages or regions on the island, to assess wether these patterns conform to known historical settlements, climatic and geographic data, sero-genetic data, dermatoglyphic data, migration data and linguistic data. The study aims also to compare results of these analyses to findings from other populations.